Digitalization of Society and the Evolution of Law: A Legal Analysis of the Use of Bitcoin and Altcoins in Commercial Transactions - Lasut, Meiske MW (PT. NALURI EDUKASI PRESS, 2025)
This study aims to analyze the legal complexity of Bitcoin and altcoin use in commercial transactions and identify the need for legal evolution to accommodate the digitalization of society. The research method uses a qualitative approach with a literature study focusing on normative legal analysis of cryptocurrency regulation, consumer protection, and the applicable legal framework. Data collection techniques were conducted through document studies of primary, secondary, and tertiary legal materials, with qualitative descriptive analysis using content analysis and a comparative approach to cryptocurrency regulation in various jurisdictions. The results show that the legal uncertainty of cryptocurrencies creates significant legal complexity in commercial transactions, where the ambiguous legal status, diverse characteristics of altcoin technology, and cross-border jurisdictional challenges require an adaptive and responsive regulatory approach. The existing consumer protection framework is inadequate to accommodate the risks of volatility, transaction irreversibility, and the complexity of blockchain technology. An adaptive regulatory model that integrates a regulatory sandbox, a principle-based approach, and a risk-based framework provides a solution to accommodate the dynamic characteristics of cryptocurrencies. This study proposes a responsive legal adaptation framework that can facilitate the co-evolution between law and blockchain technology while providing adequate protection for all stakeholders in the cryptocurrency ecosystem.